THE EFFECT OF MOZART MUSIC THERAPY ON REDUCING DYSMENORRHEA PAIN FOR ADOLESCENT IN MANSOOKO MOJOKERTO - Lestari, Indah; Suhendri, Wahyu (JURNAL KEPERAWATAN SEHAT, 2015)
The prominent physical disorder for women during menstruation is dysmenorrhea. There are several methods to reduce dysmenorrhea pain; one of them is the Mozart. Mozart music can overcome the pain based on the gate control theory that explained the pain impulse can be regulated or inhibited along the central nerve system. The aim of this research is to analyzed the effect of Mozart music on reducing dysmenorrhea pain for adolescent in MAN Sooko Mojokerto. Research design that used by researcher is pre-experimental design with one group pre-test post-test design. The populations in this research were all adolescent in tenth grade students of MAN Sooko Mojokerto. The sampling used is purposive sampling with 20 respondents were found which appropriate criteria. The collecting data is using numerical pain scale and the result processed with paired sample T-Test. From the result of paired T-Test showed that p (0,000) < α (0,05), so that, Ho refused. It means there is significant effect of Mozart music on reducing dysmenorrhea pain. This is because by listening to Mozart music can stimulate the raising of endorphin hormone that would block the release of P substance from sensory neuro, so impulse pain transmission in the spinal medulla becomes blocked, so that menstrual pain sensation is reduced.Key Words: Dysmenorrhea, Mozart Music.